Microagressão: uma análise conceitual sob a perspectiva da análise do comportamento - Barros, Micaela Acco de (2023)
The concept of microaggression was postulated in 1977 by Chester Pierce, who defined it as “subtle, stunning, often automatic and non-verbal exchanges that have the function of diminishing or despising the target”. The concept of microaggression seems to be used for situations and behaviors that are not explicitly offensive, and it has become a common concept in the social sciences, used to classify different behaviors, being applied to the most diverse social issues. The objective of this work was to carry out a behavioral analysis of the concept of microaggression based on the literature in the area. For this, a survey was carried out in the Pepsic and PsycNet databases, searching for theoretical texts that dealt with the definition of the concept of "microaggression", literature review texts on "microaggression" and research texts that contained "microaggressions" as a dependent variable. Twenty-seven texts were analyzed, considering for the behavioral analysis the contexts in which microaggression behaviors occurred, the classes of behaviors and the consequences for the targets and agents of microaggressions. As a result, we obtained three central characteristics of microaggressions: subtlety, non-intentionality, and lack of consensus for its definition, as well as three classes of microaggression behaviors: stereotyping, inferiorization and invalidation. Consequently, for the targets, it was pointed out that successive exposures throughout life to episodes of microaggression are harmful, causing psychological damage. The difficulty in identifying microaggressive behaviors generates a social clash between those who understand the harmful effects of exposure to long-term prejudices, and those who minimize these effects, normalizing these practices, making it necessary to try to define the concept of microaggression more precisely and to make itself known and discussed, through socio-educational programs and research in the area.